The Assessment of Happiness Rate of Arab Kampung Community in Malang City - Putri Nopianti; Surjono Surjono (Wacana Journal of Social and Humanity Studies, 2017)
The complexity of problems in the kampung-kota are reasonably wide from a pragmatic and practical to a more conceptual, thus the sustainable development concept of kampung-kota needs to be reviewed. One of the method for assessing kampung-kota in adapting sustainable development concept is by measuring public welfare using happiness index. On that basis, the happiness index of Kampung Arab in Malang is measured using the approach of Indonesian Central Body of Statistic (BPS) with its 10 aspects of life and the approach based on fuzzy logic. The research aims to assess the happiness index and to recommend development which may improve community’s happiness. The rating results of each aspects shows the rates of health condition at 98,71%, education and skills aspect at 72,55%, profession aspect at 75,57%, household income at 65,50%, security aspect at 69,35%, social relationship aspect at 91,36%, leisure time availability aspect at 91,65%, house condition aspect at 80,44%, the state of environment at 65,86% and the harmonious family aspect at 99,54%. One of the recommendations is that the strength in social relationships aspect in Kampung Arab can be used as the basic in the increase of other aspects trough empowering community groups and established organization.